(untitled) (Global Journal of Human-Social Science, 2017)
While inflationary sources have been linked with various issues, its attachment to money supply had especial consideration in inflation theories. The Classical version of Quantity Theory holds for inflation as being ’always and everywhere a monetary phenomenon’. On the other side, Keynes’s version departed by claiming neutrality of money in an economy where idle capacity exists. Motivated basically by these theoretical departures on the link between the two variables, and the limited availability of literatures particularly in the spirit of the subject it is concerned with, the present study aimed to empirically examine the share of money supply in explaining the dynamics of inflation in Ethiopia, using Error Correction Model by employing the time series data set for the period ranging from 1974/75 to 2014/15. The Johnson’s Maximum likelihood approach for cointegration has indicated the existence of long run relationships amongst variables entered the inflation model. Moreover, the Augmented Dickey Fuller (ADF) and Phillips Perron (PP) Unit Root tests confirmed that the variables concerned are all integrated of order one, (I(1)). ECM regression suggest that money supply, real Gross Domestic Product, trade openness, real exchange rate, budget deficit and the nominal deposit interest rate variables have together been important in explaining the long run dynamics of inflation. Except real Gross Domestic Product and nominal deposit interest rates, the effects of the remaining ones persist also in the short run. Moreover, money supply was estimated to impose the dominant effect towards validating the classical version of QTM in the context of Ethiopian economy. Besides, monetary policy is found to be more important in the dynamics of inflation compared to fiscal policy. Furthermore, VAR Granger Causality test suggests the causation running from budget deficit to money supply; and, from money supply to inflation, but no causality was suggested in reverse. This also reveals partly the applicability of the Sargent and Wallace (1981) aspect of the so called ’fiscal dominance’ in Ethiopia. Finally, the study suggests for the enhancement of effectively designed and implemented network of both monetary and fiscal policies considering the power of money supply on inflation. Moreover, investments in food and agricultural sectors could considerably support the process of ensuring price stability.